Water Softening Mechanism and Strength Model for Saturated Carbonaceous Mudstone in Panzhihua Airport, China - Ziwen Wang; Jifang Du; Shuaifeng Wu; Yingqi Wei; Jianzhang Xiao; Wenxi Han; Di Pan; Binbin Zheng (Advances in Civil Engineering)
To identify the water softening mechanisms that caused landslides in Panzhihua Airport, China, property and saturation tests of the mudstones extracted from a representative landslide were proposed. In this paper, water saturation tests were carried out on samples of carbonaceous mudstone collected from the east side of the No. 12 landslide at the airport. A number of different analytical techniques and mechanical tests were used to determine changes in chemical composition, mineral assemblages, and mudstone structural characteristics, including shear strength, after the mudstone had been softened. Three kinds of changes caused by water and three mudstone softening stages are proposed. The results show that the water has a significant influence on the properties of the mudstone, so the stability of the mudstone in the watery period is a big threat to the upper structure. A model for water immersion mudstone strength softening is developed. The model incorporates a permeability coefficient, the hydraulic gradient, and time; the model can be used to determine the mudstone’s shear strength and internal friction angle. This study provides a reference for the study of rock softened by water immersion.